2015
DOI: 10.1039/c4ra13413c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically deliverable calcium phosphate nanoparticles for localized gene expression

Abstract: Iron oxide doped tricalcium phosphate (Fe 2 O 3 @TCP) nanoparticles were designed as transfection vehicles and prepared by flame spray synthesis. Both components are known to be non-toxic and biocompatible.Calcium phosphate (CaP) facilitates DNA entry into cells without the need for toxic cationic mediators, while magnetic iron oxide allows for particle localization at a target site. Flame spray synthesis ensures easy and low-cost nanoparticle production in a reproducible way. Fe 2 O 3 @TCP nanoparticles, exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Therefore, new systems have been explored in order to achieve a more precisely controlled release of a drug when it is needed, “on demand”. Approaches used include the use of magnetic nanoparticles and pH-responsive nanoparticles [134,135,136,137]. Magnetic nanoparticles can been produced by coating their surface with iron oxide and functionalising the particles using ligands to target specific cells [135].…”
Section: Delivery Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, new systems have been explored in order to achieve a more precisely controlled release of a drug when it is needed, “on demand”. Approaches used include the use of magnetic nanoparticles and pH-responsive nanoparticles [134,135,136,137]. Magnetic nanoparticles can been produced by coating their surface with iron oxide and functionalising the particles using ligands to target specific cells [135].…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Studies have demonstrated that mineralisation can be promoted when magnetic nanoparticles act in conjunction with growth factors (e.g., BMP-2) [134]. Calcium phosphate magnetic nanoparticles have been successfully developed by Puddu et al, where tricalcium phosphate nanoparticles were doped with iron oxide by flame spray synthesis, and demonstrated a good transfection efficacy of about 40%, while maintaining 99% cell viability and a proliferation rate of over 50% [136].…”
Section: Delivery Methodsmentioning
confidence: 99%
“…As mentioned above, PEI 25K alone is cytotoxic at higher concentrations, but upon complexation with nanoparticles as observed, its cytotoxicity drops [ 42 ]. The cells incubated with PolyMag were detached and clumped, which is a clear indication of induced damage, and this cytotoxicity is most likely associated with the presence of polycations [ 44 ]. These results indicate that PEI@IONPs alone cause no significant harm to the cells and can be considered safe delivery agents inside the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that it is possible to concentrate the particles and the bound pDNA in a specific point in the cell culture plate by applying the magnetic field. They did not observe a significant toxicity but they got localized increasing in gene transfection [61]. Other groups also reported this approach using different structures of calcium phosphate and different types of magnetic materials [62,63].…”
Section: Current Studiesmentioning
confidence: 99%